“Lamp and Candle”: Classical Chinese Imagery in Taixu’s Poetry - Xiaoxiao Xu (Religions, 2023)
Taixu 太虛 (1890–1947), a prominent figure in modern Chinese Buddhism, produced a voluminous collection of poetry abounding with diverse classical Chinese images. Notably, the “lamp and candle” (dengzhu 燈燭) holds great significance, reflecting Taixu’s personal affinity with this imagery and an intimate connection to classical Chinese poetry. Acting as a potent Buddhist metaphor, it encapsulates multifaceted sentiments while also intertwining with other evocative images, such as the boat, the moon, and falling leaves. Symbolizing Taixu’s unwavering spirit, it represents his profound dedication to his craft. This article explores Taixu’s literary achievements as a poet by focusing on his adept utilization of “lamp and candle” imagery, complementing the study of his multifaceted and intricate identities. This detailed examination offers novel insights into Chinese literature and Buddhist studies, highlighting the interplay between spiritual practice and artistic expression.